CITIZEN’S SAVINGS AS A TOOL FOR THE SYSTEMIC DEVELOPMENT OF THE ECONOMY - O. S. Tenetnik (Финансы: теория и практика, 2018)
The article examines investment tools available for use by a wide range of citizens. The purpose of this paper is finding investment instruments that can perform the function of the systemic economic development. It is suggested that such tools should have the following characteristics:Are available for investment to the average citizenEnsuring a positive return after adjustments for inflation and deducting costsThe funds raised with the help of such an instrument are directed to the development of the economy.The latter feature is particularly relevant since Russia’s share in the global economy is declining as the result of slowing GDP growth.In our work, we used the following research methods: study, measurement, comparison and generalization. Thus, as a result of the study of investment instruments, we identified the advantages and disadvantages of each investment instrument. For the retrospective period, we estimated the returns, which should receive investors after adjustments to the level of inflation and costs. Further, we compared the characteristics of individual investment instruments and estimated their potential as instruments capable performing the function of systemic development of the economy. As investment tools available for use by the average citizen, there was investigated: currency, precious metals, real estate, bank deposits, deposits in micro-finance companies, securities (Federal loan bonds, corporate bonds, stocks), mutual funds, individual investment accounts opened with the professional trustee, investment life insurance. As a result, we draw conclusions concerning the potential of each instrument as a tool for the systemic development of the economy, as well as giving recommendations on the use of investment instruments, depending on the preferences of investors.